ANALISIS NILAI BUDAYA MELAYU DALAM MITOS MASYARAKAT PULAU PENYENGAT - Cyntia Evita Firawati; Dody Irawan; Tessa Dwi Leoni; Suhardi; Asri Lolita; Musliha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the Malay cultural values ​​contained in the myths of the Penyengat Island community. As an element of oral literature, myths not only function as traditional stories but also as a tool for passing on Malay cultural values ​​that reflect the Malay community's perspective on life. The approach used in this study is qualitative with a descriptive research type. The data used are myth narratives that developed in the Penyengat Island community, which were obtained through observation, interviews, and documentation. Data analysis techniques were carried out through the steps of data reduction, data presentation, and drawing conclusions. The findings of this study indicate that myths on Penyengat Island contain Malay cultural values, such as religiosity, environmental utilization, mutual assistance, advice, compassion, harmony, wisdom, honesty, and persistence. These values ​​reflect the interaction between humans with God, nature, others, and themselves. Therefore, myths not only function as cultural heritage but also as a medium for shaping the character and life guidelines of the Malay community. It is hoped that this research can contribute to efforts to preserve oral literature and increase the younger generation's understanding of local cultural values.